Nitric oxide and bone - van'T Hof, Rob J (Blackwell Science Inc, 2001)
Nitric oxide (NO) is a free radical which has important effects on bone cell function. The endothelial isoform of nitric oxide synthase (eNOS) is widely expressed in bone on a constitutive basis, whereas inducible NOS is only expressed in response to inflammatory stimuli. It is currently unclear whether neuronal NOS is expressed by bone cells. Pro-inflammatory cytokines such as IL-1 and TNF cause activation of the iNOS pathway in bone cells and NO derived from this pathway potentiates cytokine and inflammation induced bone loss. These actions of NO are relevant to the pathogenesis of osteoporosis in inflammatory diseases such as rheumatoid arthritis, which are characterized by increased NO production and cytokine activation. Interferon gamma is a particularly potent stimulator of NO production when combined with other cytokines, causing very high concentrations of NO to be produced. These high levels of NO inhibit bone resorption and formation and may act to suppress bone turnover in severe inflammation. The eNOS isoform seems to play a key role in regulating osteoblast activity and bone formation since eNOS knockout mice have osteoporosis due to defective bone formation. Other studies have indicated that the NO derived from the eNOS pathway acts as a mediator of the effects of oestrogen in bone. eNOS also mediates the effects of mechanical loading on the skeleton where it acts along with prostaglandins, to promote bone formation and suppress bone resorption. Pharmacological NO donors have been shown to increase bone mass in experimental animals and preliminary evidence suggests that these agents may also influence bone turnover in man. These data indicate that the l-arginine/NO pathway represents a novel target for therapeutic intervention in the prevention and treatment of bone diseases.